Case Report: Upadacitinib in the management of refractory urticarial vasculitis - Almaghrabi, Maan M.; Kalantan, Nadeen; Alshareef, Alhusain; Jfri, Abdulhadi (Frontiers in Medicine, 2025)
Urticarial vasculitis (UV) is a rare autoimmune condition characterized by persistent urticarial lesions with underlying small vessel leukocytoclastic vasculitis. It often presents with systemic symptoms and poses therapeutic challenges, especially in refractory cases. We report the case of a 39-year-old woman who presented with recurrent episodes of widespread, painful wheals lasting more than 24 h, along with arthralgia, myalgia, blurred vision, and fatigue. Her diagnosis was confirmed by skin biopsy, and she failed multiple lines of immunosuppressive and biologic therapies, including corticosteroids, colchicine, omalizumab, dapsone, rituximab, mycophenolate mofetil, and cyclosporine. After initiating treatment with Upadacitinib 30 mg daily orally, in combination with omalizumab and dapsone, she experienced a dramatic clinical improvement within one month, with near-complete resolution of cutaneous lesions and significant relief of systemic symptoms. This case highlights the potential role of JAK inhibitors, particularly Upadacitinib, as a novel therapeutic option in managing refractory urticarial vasculitis. Further studies are needed to evaluate its long-term efficacy and safety in this context.